Parent- and peer-related variables associated with relational aggression in middle childhood - Brown, Natalie D. (Kansas State University, 2012)
To date, the research testing the predictors of relational aggression has largely mirrored that of the more robust physical aggression literature. Similar to the physical aggression literature, research on relational aggression has focused on age and gender differences and, more recently, the possible associations between relational aggression and other variables. However, there is a lack of research investigating the parent and peer behaviors that could potentially model relationally aggressive behavior in children. The current study drew upon social-cognitive models of aggression to test such associations. Specifically, I measured parents’ use of psychological control with their children, parents’ use of manipulative behavior with their children and other adults, and peer groups’ use of relational aggression to determine whether these variables predicted children’s use of relational aggression. It was expected that the aforementioned variables would be positively associated with children’s use of relational aggression. One hundred and sixty-five fourth-, fifth-, and sixth-grade children (52% male) enrolled in public elementary schools in the Midwest participated in the study. Additionally, 137 female and 70 male caregivers also participated. The children completed questionnaires to measure a) their use of relational aggression, b) their peers’ use of relational and physical aggression, c) the cohesiveness and distinctiveness of their main group of friends, and d) their parents’ use of psychological control. The caregivers also completed questionnaires that assessed a) their behaviors toward other adults when angry, b) how they respond to their children’s misbehavior, and c) social desirability. Consistent with Social Learning Theory and the Social-Cognitive Theory of Aggression, children’s use of relational aggression was positively related to their mothers’ use of psychological control and to their peer groups’ use of relational aggression especially when that peer group was seen as relatively cohesive and distinct. In addition, children’s use of relational aggression was more strongly associated with their parents’ use of psychological control than was their peer groups’ use of relational aggression. The current study was the first to examine and compare the associations between parent- and peer-related variables and children’s use of relational aggression.
Keywords: Relational aggression; Parents; Peers; Middle childhood; Social Psychology (0451)